2012
DOI: 10.1038/nm.2965
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IL-12/IL-23 signaling reduces Alzheimer's disease–like pathology and cognitive decline

Abstract: The pathology of Alzheimer's disease has an inflammatory component that is characterized by upregulation of proinflammatory cytokines, particularly in response to amyloid-β (Aβ). Using the APPPS1 Alzheimer's disease mouse model, we found increased production of the common interleukin-12 (IL-12) and IL-23 subunit p40 by microglia. Genetic ablation of the IL-12/IL-23 signaling molecules p40, p35 or p19, in which deficiency of p40 or its receptor complex had the strongest effect, resulted in decreased cerebral am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
219
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(235 citation statements)
references
References 50 publications
12
219
0
Order By: Relevance
“…IL-23 and IL-12 share a common subunit (p40). Other studies showed that improved cognitive performance was seen after blocking p40 by antibody, and the loss of p40 had the greatest impact on the reduction of Aβ plaque burden in an AD mouse model [16,29]. IL-17 was significantly increased in the cerebrospinal fluid of individuals with AD and in the brain of an AD mouse model [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…IL-23 and IL-12 share a common subunit (p40). Other studies showed that improved cognitive performance was seen after blocking p40 by antibody, and the loss of p40 had the greatest impact on the reduction of Aβ plaque burden in an AD mouse model [16,29]. IL-17 was significantly increased in the cerebrospinal fluid of individuals with AD and in the brain of an AD mouse model [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α antagonists and ustekinumab have been shown to improve symptoms of depression [44], but whether they could improve cognitive functions in patients with psoriasis has not been investigated. Indeed, it has recently been found that inhibition of the IL-12/IL-23 pathway may attenuate cerebral amyloidosis and cognitive deficits in a mouse model of Alzheimer's disease [45]. …”
Section: Discussionmentioning
confidence: 99%
“…While astroglia are of neuroectodermal origin, microglia (MG) rely on lineagecommitted precursors in the yolk sac and are considered the brain's residential immune cells [1,36,57]. Microglia have been discussed to play pivotal roles in CNS pathologies like Alzheimer's disease, autoimmune encephalomyelitis, traumatic brain injury and ischemic stroke [4,8,32,38], where microglia fulfill their pleiotropic roles as cells of the innate immune system, including antigen presentation, phagocytosis and production of a variety of cytokines and chemokines. They have furthermore been described to be attracted to and activated by a variety of toxic or inflammatory stimuli and have been shown to initiate gliotic scar formation via secretion of respective cytokines.…”
Section: Introductionmentioning
confidence: 99%